Unemployment Reserves: Some Questions of Principle - Meriam, R. S. (Quarterly Journal of Economics, 1933)
I. The incidence of contributions from employers, 313.— Qualifications: unemployment benefits may modify competition for employment, 314; strengthening unionism introduces additional uncertainty, 315; the outcome affected by rigidity of money wage rates, 316.—Shifting forward to consumers, 316.— The assumption that employment is a function of labor costs, 317.— The incidence of a limited system of reserves, 318.— The possibility that there is no net cost, 319.— II. Employers' contributions as incentives to stabilize employment, 320.— The argument obscure and weak, 321.— The necessary conditions of additional financial incentives, 322.— Effects would be largely on casual employment, 324.— III. The form of the reserves: insurance or pooling vs. deposit or savings, 325.— Pooled reserves not true insurance, 326.— Contributions to pooled reserves akin to taxes, 330.— Pooled reserves a mixture of relief and insurance, 330, and are as unstable as industry itself, 332.— The ethics and economics of the deposit or savings basis, 333.— Conclusions, 335.